Politological Science in the Carpathian Region after the Declaration of Independence - Ihor Tsependa (Journal of Vasyl Stefanyk Precarpathian National University)
The article dwells on the state, achievements and research perspectives of the political science school of the Carpathian region scholars. It analyses the whole complex of debatable issues under study that scientists have been working on lately relying on the social demand regarding Ukrainian political processes coverage. The research revolves around certain political aspects of the general topic "Western Ukraine in the national liberation movement and in the processes of state-building". It provides analysis of the historical participation of Western Ukrainian lands in national state-building processes and in national liberation movement, ways of establishing the unity of Ukraine in the historical and political context, as well as political aspects of state-building. Political scientists of the Carpathian region have worked out a scientifically valid position condemning Russia's imperial ambitions regarding the independent Ukrainian state.